In this case, this is not simple interest. His business earns $43,200 Now.
After one year, Liam will earn $43,200 + 1.2% of $43,200. That is
43,200 + 0.012 * 43,200 = 43,200 + 518.40 = 43,718.40
For the next year, year two, he earns 1.2% more than 43,718.40. That is:
43,718 + 1.2% of $43,718.40 =
43,718.40 + 0.012 * 43,718.40 = 43,718.40 + 524.62 = 44,243.02
Every year, he earns 1.2% more than he earned the previous year. This is compound interest. We could continue calculating it year by year for 6 years, but there is a formula for compound interest.
A = P(1 + r/n)^nt
where
A = total value after adding interest
P = original principal value
r = interest rate in decimal
n = number of times interest is compounded in one year
t = number of yerars
In this case we are looking for A, and we have
P = $43,200
r = 0.012
n = 1
t = 6
A = $43,200(1 + 0.012/1)^(1*6)
A = $43,200(1.012)^6
A = $43,200(1.074195)
A = $46,405.22